2013
DOI: 10.1118/1.4791648
|View full text |Cite
|
Sign up to set email alerts
|

Proton‐minibeam radiation therapy: A proof of concept

Abstract: The high PVDR obtained for some configurations and the small penumbras in comparison with existing radiosurgery techniques, suggest a potential gain in healthy tissue sparing in this new technique. Biological studies are warranted to assess the effects of pMBRT on both normal and tumoral tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
152
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(158 citation statements)
references
References 61 publications
4
152
0
2
Order By: Relevance
“…1 as well as in the Tables 1 and 2 one may conclude that a brass collimators provide better results. The remarkable feature of the simulations is that for both collimator types high PVDR values are observed on the way from the surface to a target (tumor), while nearly homogeneous dose distribution is realized at the depth of the target (tumor) -5 cm, thus illustrating a possibility to realize this important additional advantageous feature of the hadron fractionated therapy [7].…”
Section: Monte Carlo Simulations For the Fractionated Hadron Radiatiomentioning
confidence: 85%
See 2 more Smart Citations
“…1 as well as in the Tables 1 and 2 one may conclude that a brass collimators provide better results. The remarkable feature of the simulations is that for both collimator types high PVDR values are observed on the way from the surface to a target (tumor), while nearly homogeneous dose distribution is realized at the depth of the target (tumor) -5 cm, thus illustrating a possibility to realize this important additional advantageous feature of the hadron fractionated therapy [7].…”
Section: Monte Carlo Simulations For the Fractionated Hadron Radiatiomentioning
confidence: 85%
“…The major factor is evolution of PVDR over the depth in phantom. It was pointed out in [7], that one would expect the best results from mini-beam fractionated therapy in case of such shaping of beams that PVDR produced on their way to the tumor are largest in the healthy tissue, while fractionation degrades at the depth of the tumor. The scattering of protons by the slit/holes edges as well as the contamination by the secondary products generated in the collimators makes also fractionation less pronounced.…”
Section: Monte Carlo Simulations For the Fractionated Hadron Radiatiomentioning
confidence: 99%
See 1 more Smart Citation
“…The MRT principle, originally developed for photon microbeams can also be applied using narrowly collimated and closely spaced proton beams [3,4]. Zlobinskaya et al [4] proposed microchannel diameters ranging between 50 mm and 500 mm and suggested the distance between the channels (point-to-point distance, d) to be at least 10 times larger than the microchannel radius.…”
Section: Introductionmentioning
confidence: 99%
“…Previous models for creating proton microbeams (10 mm diameter) for radiosurgery have shown that surface dose can increase to levels far above the Bragg peak dose as the beam diameter is made smaller (12)(13)(14). The potential benefits of IMPT using DSS need to be weighed against the possibility of unintentional adverse effects, such as overdosing superficial normal tissues at the entrance area of the beam.…”
Section: Introductionmentioning
confidence: 99%